(untitled) (Window of Public Health Journal, 2026)
Occupational accidents are unexpected and undesirable events in the workplace that can cause physical or mental injury, property damage, and even death. Occupational accidents are influenced by various factors, both originating from the worker and the work environment. This study aims to identify the factors associated with occupational accidents among workers at PT Maruki International Indonesia. The type of research used is quantitative research with a cross-sectional study design. The population in this study was all workers at PT. Maruki International Indonesia Makassar. The sampling technique used was purposive sampling. Data analysis was carried out univariately and bivariately using the Chi-Square test at a 95% confidence level (α = 0.05). The results showed that there was a relationship between equipment factors and the occurrence of occupational accidents (p = 0.000). Highlighting equipment factors can motivate stakeholders to take targeted safety measures, reducing accidents. Meanwhile, there was no relationship between working age and occupational accidents (p = 0.466), work fatigue with occupational accidents (p = 0.848), work environment with occupational accidents (p = 0.328), or the use of personal protective equipment (PPE) with occupational accidents (p = 0.661). This study concludes that equipment factors are related to the incidence of workplace accidents among workers at PT Maruki International Indonesia Makassar. Therefore, the company is advised to improve supervision and maintenance of work equipment and regularly educate employees about the use of PPE to minimize the risk of workplace accidents. Furthermore, workers are expected to utilize their rest periods effectively to reduce the risk of work fatigue, which can lead to workplace accidents.